A preliminary study of comprehensive behavioral intervention for tics in Chinese children with chronic tic disorder or Tourette syndrome - Xu, Wen; Ding, Qiang; Zhao, Ying; Jiang, Wenqing; Han, Jingjing; Sun, Jinhua (Frontiers in Psychiatry, 2022)
Objective To investigate the adaptability of Comprehensive Behavioral Intervention for Tics (CBIT) for a Chinese population, and evaluate the efficacy of combined CBIT and pharmacotherapy (CBIT + PT) compared to CBIT or pharmacotherapy (PT) alone for reducing tics and for improving the quality of life (QoL) in a sample of Chinese children with chronic tic disorders (CTD) and Tourette syndrome (TS). Materials and methods In this 10-week randomized controlled pilot trial, 37 outpatients aged between 6 and 16 years affected by TS and CTD were randomly assigned to receive CBIT (n = 22) or PT alone (n = 15). Considering the feasibility, the patients allocated to the CBIT treatment group could further choose whether to simultaneously take medicine voluntarily, resulting in a CBIT alone group (n = 12) and a CBIT + PT group (n = 10). Results At baseline, no significant difference was found between the three groups in the demographic and clinical characteristics (p > 0.05). All three groups showed a significant reduction in tic severity after treatment assessed by the Yale Global Tic Severity Scale (YGTSS) severity score [F(2,33) = 35.05, p < 0.001, ηp2 = 0.51], the score of the Clinical Global Impression scale for Improvement (CGI-I) [F(1,34) = 13.87, p = 0.001, ηp2 = 0.29], and YGTSS impairment score [F(2,33) = 31.71, p < 0.001, ηp2 = 0.48]. Significant interactions were found between the time-point and group in emotional functioning [F(2,29) = 4.39, p = 0.02, ηp2 = 0.23], psychosocial functioning [F(2,29) = 5.93, p = 0.007, ηp2 = 0.29], and total QoL score [F(1,34) = 3.72, p = 0.04, ηp2 = 0.20] of Pediatric Quality of Life Inventory (PedsQL 4.0) for children suggesting a significantly larger improvement in emotional functioning, psychosocial functioning, and total QoL score of the life quality in the CBIT group for children self-report. PedsQL for proxy report only showed a significant main effect of time-point in physical functioning [F(1,33) = 8.35, p = 0.01, ηp2 = 0.2], emotional functioning [F(1,33) = 10.75, p = 0.002, ηp2 = 0.25], psychosocial functioning [F(1,34) = 11.38, p = 0.002, ηp2 = 0.26], and total Qol score [F(1,34) = 13.21, p = 0.001, ηp2 = 0.29]. Conclusion CBIT is probably effective in reducing tic severity in Chinese children with tic disorders. CBIT + PT may not be superior to CBIT alone in reducing tic severity and improving quality of life. CBIT alone showed advantages in improving quality of life over CBIT + PT and PT alone. CBIT might be an appropriate treatment option for patients with tic disorder in Chinese mainland.